Amplificador de áudio classe d com modulação sigma-delta aplicado a máquinas de música jukebox - Alves, Douglas Rafael Pereira (2021)
This work aims to develop a broad project in power electronics that, in the end, aims to build a single board including an audio preamplifier, class D power amplifier and switching power supply for application in musical machines Jukebox. In recent years there has been a great expansion in the demand for rental leisure areas for parties, get-togethers and events. For the success of such events, one needs, among other things, good sound equipment with good sound quality and enough power to reach the entire audience. A jukebox adds value and guarantees users fun and entertainment. To equip a jukebox, a class D amplifier was implemented because this class has high efficiency, around 90% with good sound quality. As an auxiliary circuit for sound quality, a preamp with three-band equalizer was also developed for compensating or attenuating low, mid and high frequencies. To power this amplifier, completing the project, a high-performance switching power supply was implemented. This project will be a good option and a great differential for leisure area owners, bringing more quality fun to people. The amplifier has an oscillation around 400 kHz with two channels of 150WRMS and its energy efficiency is above 90%. The source of 127 V/220 V mains selection selection, with PWM control with switching frequency of 50 kHz and symmetrical output voltage of +40 V/-40 V. Control stages, protection circuits and power are obtained. After the prototype was implemented, tests were carried out on a bench to evaluate the performance of all stages of the circuits. Thus, it was observed that the experimental results were satisfactory. The prototype works as expected with good quality, a switched power supply and the class D amplifier yield 93,2% and 99,5%, respectively, which allows the project to be feasible both from a technical and economic point of view.